-3(4-7x)=-96

Simple and best practice solution for -3(4-7x)=-96 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(4-7x)=-96 equation:



-3(4-7x)=-96
We move all terms to the left:
-3(4-7x)-(-96)=0
We add all the numbers together, and all the variables
-3(-7x+4)-(-96)=0
We add all the numbers together, and all the variables
-3(-7x+4)+96=0
We multiply parentheses
21x-12+96=0
We add all the numbers together, and all the variables
21x+84=0
We move all terms containing x to the left, all other terms to the right
21x=-84
x=-84/21
x=-4

See similar equations:

| (7)=√5x+4 | | 2x+5=8x+(-7) | | x-68=x+126 | | 2+-3z+1=7 | | 2(2x+5)=0 | | -6d+9+20d=13d+1 | | -4p-3=-7-3p | | 10x-2x^2=-12 | | 3(v-11)=15 | | 3x^{2}-7x=12 | | 99+25.99x=34.99x | | 4(x-7)=3x−5 | | ½(6x-20)=5x+7 | | -5(5.5+3.1x)=-6.2(2.5x+1.9) | | 18x+4=19x-9 | | y+125=y+125 | | 7x+3-3=52-3 | | -7(x+2)=3x-3+3(2x-1) | | 2-(7x-2)+3x=10 | | 11(7+11x)=-36+8x | | 6x+3=-9x-3(x+18) | | 3x+6x+10+5=51 | | K+6=6+k | | -8(1-7n)=440 | | 42-3x=-54+3x | | 119=17y | | -4/x-3=7 | | 5−m4=14 | | -16+4n-19=-13n+16 | | 5x10=3x | | -6x–10=-40 | | n=5-7 |

Equations solver categories